New records of crustose Teloschistaceae (lichens, Ascomycota) from the Murmansk region of Russia - Frolov Ivan; Konoreva Liudmila (Polish Polar Research, 2016)
Twenty-three species of crustose Teloschistaceae were collected from the northwest of the Murmansk region of Russia during field trips in 2013 and 2015. Blastenia scabrosa is a new combination supported by molecular data. Blastenia scabrosa, Caloplaca fuscorufa and Flavoplaca havaasii are new to Russia. Blastenia scabrosa is also new to the Caucasus Mts and Sweden. Detailed morphological measurements of the Russian specimens of these species are provided. Caloplaca exsecuta, C. grimmiae and C. sorocarpa are new to the Murmansk region. The taxonomic position of C. alcarum is briefly discussed.